2014
DOI: 10.1363/4018414
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Coerced Sex Among Female Youth in Ghana: Roles of Family Context, School Enrollment and Relationship Experience

Abstract: Context A better understanding is needed of the variables that may influence the risk of experiencing coerced sex among adolescent females in Sub-Saharan Africa. Methods Data were collected from 700 female respondents who were interviewed in 2010 and 2012 waves of a longitudinal study of behavioral risk for HIV infection among youth aged 13–14 or 18–19 and living in two towns in southeastern Ghana. A series of logistic regression models examined the influences of household composition and wealth, four family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…In addition to our present findings, adolescent girls remain a vulnerable group in Ghana with disadvantages in intra-household food distribution and resource allocation [ 33 ], sexual violence and exploitation [ 53 ], poor education [ 54 ], more substantial burdens in their time use and less income [ 55 ]. These deprivations are known to have intergenerational effects with the nutrition and health of the adolescent girl [ 56 ], which may explain that the focus of most nutrition and public health intervention programmes for adolescents in Ghana has mostly been on girls.…”
Section: Discussionmentioning
confidence: 59%
“…In addition to our present findings, adolescent girls remain a vulnerable group in Ghana with disadvantages in intra-household food distribution and resource allocation [ 33 ], sexual violence and exploitation [ 53 ], poor education [ 54 ], more substantial burdens in their time use and less income [ 55 ]. These deprivations are known to have intergenerational effects with the nutrition and health of the adolescent girl [ 56 ], which may explain that the focus of most nutrition and public health intervention programmes for adolescents in Ghana has mostly been on girls.…”
Section: Discussionmentioning
confidence: 59%
“…Other studies in sub-Saharan Africa have reported on forced sex. For instance, among teenagers in Ghana, the prevalence of forced sex was 18% and 13% in two waves of a cross-sectional survey,28 and among women in Botswana and Swaziland, the prevalence was 10.3% and 11.4%, respectively 29. Sexual roles and gender scripts in sub-Saharan African countries influence sexual experiences including sexual assault 30.…”
Section: Discussionmentioning
confidence: 99%
“…The study is limited by the fact that the variables analyzed were based on participants' self-report, without any means of verifying. This poses the challenge of reporter and recall bias especially in relation to experience of violence in the last one year [41]. The context did not allow for the measurement of the direct health related effect of youth violence on its victims.…”
Section: Limitationmentioning
confidence: 99%